Electoral Defeat and Party Change: When do Parties Adapt? - Pacześniak, Anna; Bachryj-Krzywaźnia, Maciej; Kaczorowska, Małgorzata (Political Preferences, 2020)
Electoral defeat has sometimes been called the mother of party change, but is this reputation warranted? In this paper we investigate whether party characteristics such as government status, party systemic origins, or ideological family affect how parties respond to defeat. Examining 73 parties in 28 countries, considering party efforts to change their leadership, their programs and their organizations, we conclude that only systemic origin (post-communist vs. West European countries) is a relevant factor affecting depth of party change. Parties take some corrective actions after electoral defeat, however, they are not likely to be a wholesale reforms. Thus, it would be more accurate to describe electoral defeat as a midwife of a party change, not as its mother.